Effects of hybrid catalyst layer design on methanol and water transport in a direct methanol fuel cell. (20th September 2015) - Lee, Kise; Ferekh, Saad; Jo, Ahrae; Lee, Suwon; Ju, Hyunchul
Highlights: Using hybrid CL on both anode and cathode sides was beneficial under a higher methanol feed concentration of 4 M. Using hydrophilic CL at anode and hybrid CL at cathode was the most effective under lower methanol feed concentration of 2 M. Lower water transport coefficient was achieved using hybrid catalyst layer. The use of the hybrid CL in the cathode of PEFCs successfully enhanced the water back-flow and mitigated cathode flooding. ABSTRACT: Effective control of methanol and/or water transport inside a fuel cell is critical for achieving higher cell performance and extended durability. In this study, we present a new hybrid catalyst layer (CL) design, wherein relatively hydrophobic and hydrophilic CLs are combined, forming a hybrid-layered (hydrophobic + hydrophilic) CL structure. Specially, the fabrication of relatively hydrophobic CL is realized by using a hydrophobic binding agent, i.e., polytetrafluoroethylene (PTFE), with conventional hydrophilic CL binders such as Nafion ® . In order to investigate the effect of using the hybrid CL design on fuel cell performance, several membrane electrode assemblies with different CL arrangements were fabricated and applied to direct methanol fuel cells and hydrogen polymer electrolyte fuel cells. The cell polarization and net water transport flux were measured and a comparison of the experimental data clearly indicated that the hybrid CL design had a significant influence on methanol and water transport phenomena and, consequently, on cell performance. The higher cell performance and stronger water back-flow from the cathode and anode were achieved when the hybrid CL was employed in both cathode and anode sides. This study demonstrates that controlling the spatial variation of CL wettability is effective for attaining favorable methanol and water profiles inside fuel cells.